2018
DOI: 10.3390/su10114121
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Verification of a New Corporate Sustainability Assessment Method for Manufacturing: A Multiple Case Research Study

Abstract: This paper aims at answering the question of how to design a theoretically sound corporate sustainability assessment (CSA) method that can strengthen the ability of manufacturing companies to contribute to global sustainable development (SD). In our effort to answer this question, we conduct a case study to test a newly designed CSA method to develop assessment tools for each of four different case companies. The method combines criteria-based indicators development with qualitative system dynamics modeling ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 112 publications
(182 reference statements)
1
7
0
Order By: Relevance
“…This case highlights the significant interplay between the home and host country contexts, which illustrates the complexity of how global multinationals approach CSAs. The case conforms with expectations set in the extant literature, including the importance of company commitments to sustainability standards and guidelines (i.e., GRI, UNGC and CDP) and the significant influence in directing the development of the sustainability principles, goals and issues (i.e., [30,39,44]). Yet, it is evident that the subsidiary extends beyond the headquarters commitments, demonstrating significant autonomy and proactiveness in their sustainability approach.…”
Section: Sustainability Governance System: a Nexus Between Headquartesupporting
confidence: 76%
See 2 more Smart Citations
“…This case highlights the significant interplay between the home and host country contexts, which illustrates the complexity of how global multinationals approach CSAs. The case conforms with expectations set in the extant literature, including the importance of company commitments to sustainability standards and guidelines (i.e., GRI, UNGC and CDP) and the significant influence in directing the development of the sustainability principles, goals and issues (i.e., [30,39,44]). Yet, it is evident that the subsidiary extends beyond the headquarters commitments, demonstrating significant autonomy and proactiveness in their sustainability approach.…”
Section: Sustainability Governance System: a Nexus Between Headquartesupporting
confidence: 76%
“…As [29] recently postulated, CSA is "a platform from which the private sector can implement systematic processes to address sustainability" [29] (p. 1). Indeed, [30] (p. 3) argue that sustainability assessment at the company level can be seen as "an instrument to evaluate organisational performance to assist decision-makers in determining which actions should or should not be taken in an attempt to contribute to sustainable development". A range of research has shown the broader utility of CSA supporting the private sector to engage with sustainable development (e.g., [1,16,29,31]).…”
Section: Literature Review: Corporate Sustainability Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observing the table above, there is an emphasis on corporate sustainability by organizations. [77][78][79][80][81][82] It is also possible to observe evaluations about the term NC as the focus of 6 types of research. 44,[83][84][85][86][87] Furthermore, in the research by Zijp et al 88 and Mondelaers, van Huylenbroeck and Lauwers, 89 and Kelly et al 90 the theme of sustainability related to the agricultural process had an emphasis.…”
Section: Content Analysis By Articlementioning
confidence: 99%
“…In contrast, Muñoz-Torres et al [ 36 ] specifically devised a supply chain sustainability assessment tool, although they provided scant details on the framework and its links to the SDGs. Moldavska and Welo [ 37 , 38 ] have developed and refined an SDG assessment method, in which an organizational model is first constructed. An external sustainability expert (with limited company influence) links the relevant criterion for sustainable manufacturing and the SDGs.…”
Section: Sdgs As a Guide In The Sustainability Transitions Of Businesmentioning
confidence: 99%